Waste Inventorization Inorganic In The Mangrove Ecosystem Bunaken Island For The East Part - Sundah, Geraldo Thimoty; Schaduw, Joshian N. W.; Warouw, Veibe; Kumampung, Deislie R.H.; Paransa, Darus Sa'adah J.; Mokolensang, Jeffrie (Sam Ratulangi University, 2021)
The coastal area is a potential resource in Indonesia, is an intermediate area between the mainland and Ocean. This resource is very large which is supported by the existing coastline 81,000 km long. Long coastline This holds the potential for a large wealth of natural resources. The potential including biological and non-biological potential. in addition to the potential for natural resources that are widespread on the coast of Indonesia, potential pollution to the coastal and marine environment has quite a big opportunity. this opportunity could be caused by Indonesia's population density, high tourist activity including transportation, and major construction. As for the goal This study aims to identify the type and amount of waste inorganic in the Bunaken coastal mangrove ecosystem in the eastern part and identify the size and weight characteristics of inorganic waste in the mangrove ecosystem. The method used The result of this research is the coastline survey method methodology based on NOAA (2013) and line transects with taking 2 stations. This research was conducted for three months, which at each station has 1 transect line, each of which has 5 plots/sampling plots. Transect lines are carried out in parallel coastline along 50 meters of trash in the mangrove forest the distance between stations is 50 m, where the transect line must be located represents the research area. The data taken next is back analysis with the help of a computer program MS Excel The types of marine debris found at the research location are plastic, rubber, metal, and glass waste. The total size of the litter type which was found at the research location showed 2 characteristics, namely mega- debris and macro-debris. The most dominant type of waste is plastic waste.Keywords: Inorganic waste, Mangrove, East BunakenAbstrakÂ Wilayah pesisir yang merupakan sumber daya potensial di Indonesia, adalah daerah peralihan antara daratan dan lautan.Sumber daya ini sangat besar yang didukung oleh adanya garis pantai sepanjang sekitar81.000 km. Garis pantai yang panjang ini menyimpan potensi kekayaan sumber alam yang besar.Potensi itu diantaranya potensi non hayati dan hayati.Disamping potensi sumberdaya alam yang tersebar luas di pesisir Indonesia, potensi pencemaran terhadap lingkungan pesisir dan laut pun memilik i peluang yang cukup besar.Peluang ini dapat disebabkan oleh padatnya penduduk Indonesia, aktifitas wis ata yang cukup tinggi termasuk transportasi, dan pembangunan yang besar. Adapun tujuan dari penelitian ini yaitu Mengidentifikasi jenis dan jumlah sampah anorganik yang berada di ekosistem mangrove pantai Bunaken bagian timur Dan Mengidentifikasi karakteristik ukuran dan berat sampah anorganik pada ekosistem mangrove. Metode yang dipakai dalam hasil penelitian ini adalah metode shoreline survey methodology berdasarkan NOAA (2013) dan Line transect dengan mengambil 2 stasiun . Penelitian ini dilaksanakan selama tiga bulan, dimana dalam setiap stasiun terdapat 1 line transect yang masingâ€“masing memilik i 5 petak/plot pengambilan sampel. Jalur transek dilakukukan sejajar garis pantai sepanjang 50 meter adanya sampah pada mangrove jarak antar stasiun adalah 50 m, dimana jalur transek tersebut harus mewakili wilayah penelitian. Data yang di ambil selanjutnya d i analisa kembali dengan bantuan program komputer MS Excel Jenis sampah laut yang ditemukan pada lokasi penelitian berupa sampah plastik, karet, logam, dan kaca. Jumlah ukuran jenis sampah yang terdapat di loksasi penelitian menunjukan bahwa terdapat 2 karakteristik yaitu mega-debris dan macro-debris. Jenis sampah yang paling dominan adalah sampah plastik.Kata Kunci: Sampah Anorganik, Mangrove, Bunaken Timur.